Perancangan Media Pelatihan Digital Marketing Untuk Peningkatan UMKM Berbasis Website - Muhammad Alwi Hafizh; Furqan Khalidy; Saiful Amir; Mardiah Mardiah (LKP Unity Academy, 2025)
The internet is widely used in today's digital era. With the internet, people around the world communicate in a virtual platform called Social Media such as Facebook, Instagram, Twitter and TikTok. With Social Media, a business actor (MSME) can market their products locally, nationally and even internationally so that they can increase sales. Marketing via social media is also called digital marketing. There are still many MSMEs in Medan City who do not understand digital marketing techniques, so it is necessary to provide training to Medan City MSMEs. However, the large costs of offline training hinder the implementation of the training. For this reason, a web-based training media was developed so that training is carried out online so that training costs can be efficient. Development of digital marketing training media using Codeigniter 3.0 and is only intended for Medan city MSMEs.